Fly, dumbo, fly!: a little story for little learners - Liberts, Jennifer; LoRaso, Carlo Kurtz, John (Parragon Bath, 2012)
"Fly, Dumbo, Fly! A Little Story for Little Learners" is a sweet children's book that tells the story of Dumbo, the beloved elephant with oversized ears. This narrative focuses on Dumbo's journey of self-discovery and the importance of believing in oneself. Through engaging illustrations and simple language, the book conveys messages about courage, friendship, and embracing one's unique traits. It's designed to inspire young readers to overcome challenges and recognize their own potential, making it a delightful read for early learners.